Users That Do Personalizing Activity Toward Their Belonging - Yunidar, Dandi; Majid, Ahmad Zuhairi Abdul (2017)
This research is based on the belief that "the Asian people prefer more colourful interfaces with images rather than plain interfaces" (Tzvetanova, 2007).The previous research conducted by Tzvetanova was about interface, the question is what if it's a three dimensional from of daily use product?